2022
DOI: 10.3389/fsurg.2022.811023
|View full text |Cite
|
Sign up to set email alerts
|

The Global States and Hotspots of ERAS Research From 2000 to 2020: A Bibliometric and Visualized Study

Abstract: BackgroundEnhanced recovery after surgery (ERAS) protocol has been implemented in surgeries for more than 20 years, this study investigated the global states and hotspots of ERAS research.MethodsBased on the Web of Science database, a bibliometric and visualized study of original ERAS research from 2000 to 2020 was performed, including the trends of publications and citations; distribution of countries, authors, institutions, sources; study design, level of evidence, served surgeries and surgical disciplines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Despite using an inclusive and comprehensive search strategy the number of existing studies on the implementation of ERAS protocols in Africa is very low, as we were only able to nd a few studies (n = 15) and they were limited to certain geographical locations, as most of these studies were conducted in Egypt (n = 10) and South Africa (n = 4). This nding is also consistent with a study of the global distribution of ERAS research, which found that most studies have been conducted in high-income countries (11). Furthermore, the implementation efforts were mostly in obstetric and gynecological procedures (n = 7).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite using an inclusive and comprehensive search strategy the number of existing studies on the implementation of ERAS protocols in Africa is very low, as we were only able to nd a few studies (n = 15) and they were limited to certain geographical locations, as most of these studies were conducted in Egypt (n = 10) and South Africa (n = 4). This nding is also consistent with a study of the global distribution of ERAS research, which found that most studies have been conducted in high-income countries (11). Furthermore, the implementation efforts were mostly in obstetric and gynecological procedures (n = 7).…”
Section: Discussionsupporting
confidence: 90%
“…However, the evidence on the implementation of ERAS practice in Africa is very limited (11), and most reports from the region are from small-scale studies or anecdotal reports. Additionally, resource constraints may further hinder the widespread implementation of ERAS in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative patients then received personally tailored rehabilitation services from the rehabilitation experts within our department, rather than transferring to the rehabilitation department or hospital. Of note, per our standard protocol, we applied a conventional rehabilitation program for these patients, instead of the Enhanced Recovery After Surgery (ERAS) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%